Interfacial profile and propagation of frontal photopolymerization waves - Vitale,A; Hennessy,MG; Matar,OK; Cabral,JT (Macromolecules, 2014)
We investigate the frontal photopolymerization of a thiol–ene system with a combination of experiments and modeling, focusing on the interfacial conversion profile and its planar wave propagation. We spatially resolve the solid-to-liquid front by FT-IR and AFM mechanical measurements, supplemented by differential scanning calorimetry. A simple coarse-grained model is found to describe remarkably well the frontal kinetics and the sigmoidal interface, capturing the effects of UV light exposure time (or dose) and temperature, as well as the front position and resulting patterned dimensions after development. Analytical solutions for the conversion profile enable the description of all conditions with a single master curve in the moving frame of the front position. Building on this understanding, we demonstrate the design and fabrication of gradient polymer materials, with tunable properties along the direction of illumination, which can be coupled with lateral patterning by modulated illumination or grayscale lithography.